Evaluation of deep geothermal exploration drillings in the crystalline basement of the Fennoscandian Shield Border Zone in south Sweden - Rosberg, Jan Erik; Erlström, Mikael (Geothermal Energy, 2021)
The 3.1- and 3.7-km-deep FFC-1 and DGE-1 geothermal explorations wells drilled into the Precambrian crystalline basement on the southern margin of the Fennoscandian Shield are evaluated regarding experiences from drilling, geological conditions, and thermal properties. Both wells penetrate an approximately 2-km-thick succession of sedimentary strata before entering the crystalline basement, dominated by orthogneiss, metabasite and amphibolite of the (1.1–0.9 Ga) Eastern Interior Sveconorwegian Province. The upper c. 400 m of the basement is in FFC-1 severely fractured and water-bearing which disqualified the use of percussion air drilling and conventional rotary drilling was, therefore, performed for the rest of the borehole. The evaluation of the rotary drillings in FFC-1 and DGE-1 showed that the average bit life was very similar, 62 m and 68 m, respectively. Similarly, the average ROP varied between 2 and 4 m/h without any preferences regarding bit-type (PDC or TCI) or geology. A bottomhole temperature of 84.1 °C was measured in FFC-1 borehole with gradients varying between 17.4 and 23.5 °C/km for the main part of the borehole. The calculated heat flow varies between 51 and 66 mW/m2 and the average heat production is 3.0 µW/m3. The basement in FFC-1 is, overall, depleted in uranium and thorium in comparison to DGE-1 where the heat productivity is overall higher with an average of 5.8 µW/m3. The spatial distribution of fractures was successfully mapped using borehole imaging logs in FFC-1 and shows a dominance of N–S oriented open fractures, a fracture frequency varying between 0.85 and 2.49 frac/m and a fracture volumetric density between 1.68 and 3.39 m2/m3. The evaluation of the two boreholes provides insight and new empirical data on the thermal properties and fracturing of the concealed crystalline basement in the Fennoscandian Shield Border Zone that, previously, had only been assessed by assumptions and modelling. The outcome of the drilling operation has also provided insight regarding the drilling ...